Desain Media Pembelajaran Interaktif Berbasis Powerpoint & Ispring Terhadap Kemampuan Berpikir Kreatif Siswa Kelas VI - Tarmidzi, Tarmidzi; Tresnawati, Nailah; Oktaverina, Meigy Irma (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2024)
The aim of this study is to determine the validity of the design of interactive learning media based on PowerPoint & iSpring and the improvement in students' creative thinking skills before and after learning using these interactive media. This research is motivated by observations of sixth-grade elementary school students, indicating that both face-to-face and online learning processes are monotonous and lack variety. Learning does not utilize media and does not focus on student engagement, leading to boredom and fatigue among students. Moreover, students struggle to understand the material, especially on the topic of puberty. This study was a type of design research, with the subjects being sixth-grade elementary school teachers as media validators, and sixth-grade elementary school students in Cirebon Regency. The results show that interactive learning media based on Microsoft PowerPoint & iSpring Suite 9 are valid, practical, and effective, meaning they are suitable for use with sixth-grade elementary school students. Additionally, there is an improvement in students' creative thinking skills between the pre-test and post-test using these interactive learning media